2017
DOI: 10.1007/s00122-017-2916-2
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the complex nature of bolting time regulation in Beta vulgaris

Abstract: Only few genetic loci are sufficient to increase the variation of bolting time in Beta vulgaris dramatically, regarding vernalization requirement, seasonal bolting time and reproduction type. Beta species show a wide variation of bolting time regarding the year of first reproduction, seasonal bolting time and the number of reproduction cycles. To elucidate the genetics of bolting time control, we used three F mapping populations that were produced by crossing a semelparous, annual sugar beet with iteroparous, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
7
0
1
Order By: Relevance
“…The expression of the flowering-related genes BTC1 and BBX19 in taproot tissue suggested that taproots might also be involved in the perception of vernalization. It is tempting to think into a direction where newly identified (Pfeiffer et al, 2014;Broccanello et al, 2015;Tränkner et al, 2017) or yet undiscovered bolting loci might harbor yet uncharacterized factors which might integrate both, bolting and required sink-source transition, similar to the recently described FT homolog StSPS6A ('tuberigen') in potato (Navarro et al, 2011;Abelenda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the flowering-related genes BTC1 and BBX19 in taproot tissue suggested that taproots might also be involved in the perception of vernalization. It is tempting to think into a direction where newly identified (Pfeiffer et al, 2014;Broccanello et al, 2015;Tränkner et al, 2017) or yet undiscovered bolting loci might harbor yet uncharacterized factors which might integrate both, bolting and required sink-source transition, similar to the recently described FT homolog StSPS6A ('tuberigen') in potato (Navarro et al, 2011;Abelenda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, BvFT2 was proposed as a candidate gene for seasonal bolting time at the SBT-4 locus (Tränkner et al, 2017 ). We identified two and five polymorphisms within BvFT2 and BvFT1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The SBT-9 / BR1 locus was discovered to control bolting resistance after winter (Pfeiffer et al, 2014 ), where a homolog of the Arabidopsis CLEAVAGE AND POLYADENYLATION SPECIFIC FACTOR 73-I ( CPSF73-I ) was identified as the most promising candidate gene (Tränkner et al, 2016 ). Recently, Tränkner et al ( 2017 ) proposed that two QTL contribute to variation in seasonal bolting. Besides SBT-9 / BR1 , the SBT-4 locus was elucidated to majorly control seasonal bolting and BvFT2 was suggested as a candidate gene.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait loci (QTL) and major genes controlling bolting time have been mapped to the nine beet chromosomes 2 . The bolting time QTL SEASONAL BOLTING- 4 and -9 ( SBT-4, SBT-9 ) accounts for up to 52% of the phenotypic variation 3 . The phenotypic effect of SBT-4 is likely caused by the major flowering time regulator BvFT2 because they were mapped to the same position on chromosome 4.…”
Section: Introductionmentioning
confidence: 99%